Perilaku Fraud dalam Kerangka Fraud Triangle : Survey Pada Aparatur Pemerintah Desa - Aidah Ibrahim; Sufiati; Pura, Rahman (Insan Cita Bongaya Research Journal, 2024)
This study aims to analyze the influence of fraud triangle on fraud behavior in village governments. The survey was conducted. The population of this study is the total number of Village Officials in Central Adonara District, East Flores Regency, a total of 65 Village Officials, while the sample taken is 65 respondents using the saturated sample technique. The data collection technique uses questionnaire techniques and data analysis techniques use multiple linear regression. The results of the study show that pressure, opportunity and rationalization have a positive and significant effect on fraud behavior.